2012
DOI: 10.1155/2012/309494
|View full text |Cite
|
Sign up to set email alerts
|

Selective Estrogen Receptor Modulators Regulate Dendritic Spine Plasticity in the Hippocampus of Male Rats

Abstract: Some selective estrogen receptor modulators, such as raloxifene and tamoxifen, are neuroprotective and reduce brain inflammation in several experimental models of neurodegeneration. In addition, raloxifene and tamoxifen counteract cognitive deficits caused by gonadal hormone deprivation in male rats. In this study, we have explored whether raloxifene and tamoxifen may regulate the number and geometry of dendritic spines in CA1 pyramidal neurons of the rat hippocampus. Young adult male rats were injected with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 85 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…While functional outcomes were not addressed in the current study, the findings nevertheless suggest that SERMs may have the capacity to enhance structural and behavioral recovery following ischemic brain injury. In support of this possibility, both raloxifene and tamoxifen have been reported to acutely enhance spine density in the hippocampus and prefrontal cortex of normal non-ischemic male rats, an effect that was correlated with enhanced allocentric working memory [12, 13]. The molecular mechanisms underlying raloxifene and tamoxifen regulation of sine density in the cerebral cortex is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While functional outcomes were not addressed in the current study, the findings nevertheless suggest that SERMs may have the capacity to enhance structural and behavioral recovery following ischemic brain injury. In support of this possibility, both raloxifene and tamoxifen have been reported to acutely enhance spine density in the hippocampus and prefrontal cortex of normal non-ischemic male rats, an effect that was correlated with enhanced allocentric working memory [12, 13]. The molecular mechanisms underlying raloxifene and tamoxifen regulation of sine density in the cerebral cortex is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies suggest that tamoxifen and raloxifene can have neuroprotective effects in vitro or in vivo against neurological insults or in neurological disorders [111]. Additionally, both tamoxifen and raloxifene have also been shown to enhance memory, cognition, and synaptic plasticity in various experimental studies [12, 13]. However the mechanisms underlying the beneficial neural effects of SERMs are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Raloxifene, a second-generation selective estrogen receptor modulator, is approved for use in the treatment of osteoporosis in postmenopausal women and for breast cancer in women and can have beneficial effects on brain function including increased cortical plasticity. 39 , 40 Studies have reported that raloxifene at a daily dose of 120 mg preserved neural activity during a memory challenge in healthy aging men 41 and preserved cognition in postmenopausal women. 42 Recent clinical trials and case reports have shown that adjunctive raloxifene at 60 or 120 mg is beneficial for the treatment of positive, negative and general psychopathology symptoms in postmenopausal women with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol and testosterone were shown to regulate dendritic length and the density of spines in the spinal cord nucleus of the bulbocavernosus (SNB), VMH, ARH, medial amygdala, striatum, cortex and hippocampus ([5, 17, 26, 34, 45, 48, 50, 69, 70, 7981, 115, 147, 151]; see Luine et al and MacLusky et al, this volume). The most dramatic effects of estradiol on neuronal number and morphology occur during development, but significant steroid regulation of dendritic structure also occurs in adulthood.…”
Section: Introductionmentioning
confidence: 99%